Psychobiological issues in substance use and misuse - Murphy, Philip N. (New York : Routledge, 2021)
"In this book, Murphy brings together a team of international experts to review cutting-edge scientific literature from the field of psychobiology which addresses important questions and broadens our understanding of substance use behaviours. The reader is introduced to the multi-faceted nature of substance use and misuse, and its growing need to be discussed across diverse disciplines and perspectives. The book also addresses important questions regarding public policy and professional practice in the context of different social and cultural environments, and comments on the methodological and ethical approach in substance use and misuse. Chapters explore a spectrum of substances, which include: cocaine, alcohol, ecstasy (MDMA), methamphetamine, synthetic cannabinoids, tobacco, ketamine, novel psychoactive substances, and vaping products. The use of these substances poses important questions for science and for society. This book is written to help academics, practitioners, and students in a variety of academic and professional disciplines answer those questions while staying up to date with the psychobiological literature. This is a vital resource for professionals and upper-level undergraduate and postgraduate students undertaking research in areas related to biological psychology, biology, health studies, and medicine"--
OCLC-licensed vendor bibliographic record.
Keywords: Substance abuse -- Psychological aspects; Substance abuse -- Prevention; Substance abuse -- Treatment; Drug abuse -- Prevention; Drug abuse -- Treatment; PSYCHOLOGY / Physiological Psychology; PSYCHOLOGY / Neuropsychology; PSYCHOLOGY / Psychopathology / Addiction